Emerging Antibiotic Resistance in Streptococcus Pneumonia and Haemophilus Influenzae in Paediatric Pneumonia - Ansari, Md. Ashfaque; Jha, Anand Kumar; Gupta, Ravi Shankar; Yadav, Tapeshwar (Nepal Journal of Health Sciences, 2025)
Introduction: Pneumonia is the leading cause of death in children under five, primarily caused by Streptococcus pneumonia and Haemophilus Influenza. The emerging antibiotic resistance observed in the commonly occurring pathogens is a major challenge compromising the treatment procedure. Objective: To determine the prevalence and evaluate the antibiotic susceptibility patterns of S. pneumoniae and H. influenzae isolated from paediatric pneumonia patients. Methods: This was a hospital and lab-based prospective observational study conducted from 29th March 2024 to 28th March 2025 at National Medical College Teaching Hospital. A total of 150 children under the age of 15 with confirmed presence of S. pneumoniae or H. influenza in blood or sputum culture are included in the study. Data were entered and analyzed in Microsoft Excel 2016 and SPSS version 27. Descriptive findings were presented in table including frequency, percentage, mean and standard deviation. Results: The high resistance rates to commonly used antibiotics such as ceftriaxone and ampicillin, particularly among S. pneumoniae (63% resistance to ceftriaxone) and H. influenzae (55% resistance to ampicillin), are alarming. The Minimum Inhibitory Concentration -based susceptibility testing shows the ceftriaxone crossing the resistant breakpoint, indicating true resistance and not just tolerance. Similarly, elevated Minimum Inhibitory Concentrationin azithromycin and ampicillin-resistant strains indicate emerging resistance trends in pediatric pneumonia pathogens, especially against commonly used beta-lactam and macrolide antibiotics. The need for regular local antibiogram updates and reconsideration of empirical therapy guidelines is evident. Conclusions: The findings underline the urgent need to reconsider current empirical treatment protocols and promote rational antibiotic use in clinical settings.